2009
DOI: 10.1111/j.1365-2516.2008.01978.x
|View full text |Cite
|
Sign up to set email alerts
|

Stability, efficacy, and safety of continuously infused sucrose‐formulated recombinant factor VIII (rFVIII‐FS) during surgery in patients with severe haemophilia

Abstract: Bolus injection (BI) of sucrose-formulated recombinant factor VIII (rFVIII-FS) is an approved treatment for haemophilia patients undergoing major surgery. Continuous infusion (CI) during surgery has potential benefits by providing steady administration of replacement factor to the patient, avoiding high peaks and low troughs. We tested the stability of rFVIII-FS under CI conditions and conducted a single-centre, open-label, phase III study to evaluate the efficacy and safety of CI using rFVIII-FS in haemophili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
53
0
1

Year Published

2010
2010
2014
2014

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(61 citation statements)
references
References 24 publications
7
53
0
1
Order By: Relevance
“…The complete set of collected data is summarized in Table 1. A total of 60 publications were included representing mice, dogs, and humans with HA as well as normal mice, rats, rabbits, and monkeys 7–11,14–16,25–76. A summary of the NCA derived PK parameters CL, V ss , MRT, and half‐life ( t 1/2 ) are presented in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…The complete set of collected data is summarized in Table 1. A total of 60 publications were included representing mice, dogs, and humans with HA as well as normal mice, rats, rabbits, and monkeys 7–11,14–16,25–76. A summary of the NCA derived PK parameters CL, V ss , MRT, and half‐life ( t 1/2 ) are presented in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…Martinowitz et al. [4] reported that continuous infusion of sucrose‐formulated recombinant FVIII is stable, effective and safe during major surgery within 24 h. Lee et al. [3] described that continuous infusion was a cost‐effective delivery system with the portable minipumps, as approximately 30% of the total consumption of the concentrate can be saved, when compared with intermittent bolus infusion.…”
Section: Discussionmentioning
confidence: 99%
“…Also, many clinical success results were reported using continuous infusion [1–5]. In those reports, the continuous infusion speed was from 2.0 to 6.0 IU kg −1 h −1 when the desired factor level was aimed at 1.0 IU mL −1 .…”
Section: Introductionmentioning
confidence: 99%
“…Such minor amounts of heparin neither influence the stability of the reconstituted FVIII and FIX [1,25] nor affect in-vivo hemostasis achieved by CI. In some products, addition of heparin may even improve stability, as in the case of rFVIII-FS [16]. In contrast, the addition of unfractionated heparin (UH) to rFVIIa leads to rarely, short-and/or long-term prophylaxis.…”
Section: Prevention Of Thrombophlebitismentioning
confidence: 99%
“…From[16]. Mean per cent recovery ±SD for rFVIII-FS activity based on activity from the time zero level following reconstitution of the concentrate.…”
mentioning
confidence: 99%